An evaluation of community pharmacists' perception of e-cigarette: An English cross-sectional survey with geospatial analysis. - Ravina Barrett; Louise Vythelingum (University of Huddersfield Press, 2022)
We wanted to establish prevalence of e-cigarette sale via English community pharmacies. A cross-sectional survey of 500 retail-pharmacies was completed. Seventeen out of the 66respondents sold e-cigarettes, indicating a sales-prevalence of 25.76%. NRT was widely available for sale (n=16, 94.1%), cessation services were less frequently available (n=7, 41.2%), or not available (n=9, 52.9%). 'Daily smokers' were likely to use e-cigarette (n=8, 47.1%). Accessories were sold to0-2 people (n=13, 76.5%), χ² p=2.454 x 10-4. Young women purchased e-cigarettes (n=4, 23.5%), p=0.049, which were placed on top of the counter (n=7,41.2%), reflecting 'impulse sales' strategy. NRT was available for self-selection (n=14, 82.4%) (p=0.004), however staff-assistance was required(n=12, 70.6%), posing barriers. Costs for e-cigarette (£10.99-£29.99) versus NRT (£4.25-£35.99) represents value for money. Labelling and packaging were found to be attractive, p=0.049, fashionable, colourful p=0.049, healthy, potentially breaching laws. All respondents provided NRT counselling, p<1x10-8.Less than half (n=8, 47.1%) provide e-cigarette's counselling, while a majority(n=9, 52.9%) did not. Eight respondents describe 22 flavours, providing good mouth feel. Aggregate 'deprived' versus 'affluent' analysis revels interesting insights. We find some support of non-smokers initiating use. Pharmacists help patients but have limited support. We make recommendations to improve practice.